Dimensions Of Future Education For Kindergarten Teachers (Journal of the College of Basic Education, 2024)
Futuristic education or the vision of the future in education is that it occupies a fundamental position in the process of change in human society. The individual faces a large group of changes that have a clear impact on his future. The process of orienting the future is considered a process inherent to the individual since the beginning of creation. Future education and its dimensions are for the development and development of a society that aspires to progress. Education is considered essential. Education, whether as a variable for societal transformation or a primary driver of this transformation, is by virtue Its role and nature are the aspects of society most vulnerable to change. Accordingly, the severe changes that the future entails and the challenges it imposes will necessarily bring about violent changes in the education system, its philosophy, politics, role, institutions, curricula, and methods.The current research aimed to identifyDimensions of future education among kindergarten teachers:To achieve the goals, the researcher did the following I adopted the Future Education Dimensions Scale (Wriosh) 2019 which consists of (64) items. The researcher verified the discriminant power and internal consistency, and the researcher extracted reliability using the Cronbach’s alpha method, as it reached (0.85).The research results concluded that.Kindergarten teachers do not enjoy the scientific and future dimension, as the difference was not statistically significant.The researcher made some recommendations The role of the Ministry of Education is to encourage and strengthen kindergarten teachers by providing all the supplies and capabilities that help them in teaching children. Work to pay attention to all future dimensions of teachersThe researcher came up with some suggestions A similar study on university students in all majors and for both genders, males and females A study aimed at building a program to develop the scientific dimension and the educational dimension for kindergarten teachers.